THE INFLUENCE OF INVESTMENT AND REGIONAL TAX REVENUE ON ECONOMIC GROWTH OF EAST JAVA PROVINCE IN 2018-2022 - Aprilisa, Nursyifa; Iranto, Dicky; Mukhtar, Saparuddin (Universitas Serambi Mekkah, 2024)
East Java Province is one of the regions experiencing very good economic growth. East Java Province is an autonomous region of Indonesia which has certain territorial boundaries with the second largest population in Indonesia, namely in 2022 there will be 41.150.000 people. As the population in East Java Province increases, the opportunities for expanding markets and specializing the economy will also be large. This indicates that East Java Province has experienced achievements in implementing regional development in the economic sector. With this comprehensive and sustainable development, the existence of East Java Province can influence the achievement of development results in East Java Province. This research uses the panel data regression method with the E-views 12 analysis tool. The results of this research show that investment and regional tax revenue have a positive and significant effect on economic growth.